General practice physician knowledge about headache: evaluation of the municipal continual medical education program Conhecimento dos médicos generalistas sobre cefaléias: avaliação de um programa municipal de educação médica continuada - Pedro André Kowacs; Carlos Alexandre Twardowschy; Élcio Juliato Piovesan; Renata Dal-Prá Ducci; Raphael Henrique Déa Cirino; Fátima Hamdar; Eliane Regina da Veiga Chomatas; Inês Kultchek Marty (Arquivos de Neuro-Psiquiatria, 2009)
OBJECTIVE: Headache is a common condition not always managed satisfactorily by primary care providers (PCPs). In an effort to improve headache care, the Curitiba City Hall in consortia with Hospital de Clínicas da Universidade Federal do Paraná - Brazil developed an educational program directed to the PCPs. The goal of the project was to evaluate, to update and to train the PCP on headache knowledge and care. METHOD: The program was designed to have a theoretical phase and a practical phase. Knowledge on headache and medical care of headache were surveyed before and after the theoretical phase thorough a specific questionnaire. RESULTS: Significant improvement in post-CME scores on headache prevalence (p<0.001), migraine diagnosis (p<0.001) and management (p=0.01), secondary headache diagnosis (p=0.005) and management (p=0.005) was reached by the respondents. CONCLUSION: Improvement in post-CME scores confirms that the program had a significant immediate impact on the PCPs knowledge directly affecting the patient's health. OBJETIVO: Cefaléia é uma condição comum nem sempre tratada de forma adequada pelos médicos generalistas (MG). Com o objetivo de melhorar essa situação, a Prefeitura de Curitiba em parceria com o Hospital de Clínicas da Universidade Federal do Paraná - Brasil desenvolveu um programa para os MG. O objetivo principal desse projeto foi avaliar, atualizar e capacitar médicos a respeito do conhecimento e manejo das cefaléias. MÉTODO: O programa consistiu de uma fase teórica e uma fase prática. O conhecimento sobre cefaléia e seu manejo foi avaliado através de um questionário específico antes e depois da fase teórica. RESULTADOS: Significativa melhora no pós-teste nos itens de prevalência de cefaléias (p<0,001), diagnóstico de migrânea (p<0,001) e seu manejo (p=0,01), diagnóstico de cefaléia secundária (p=0,005) e seu manejo (p=0,005) foram alcançados pelos participantes. CONCLUSÃO: Melhorias na pontuação dos pós-testes confirmam que o programa teve um impacto imediato e significante no conhecimento dos MG afetando diretamente a saúde dos pacientes.